2012
DOI: 10.3892/ol.2012.996
|View full text |Cite
|
Sign up to set email alerts
|

Tendencies for higher co-expression of EGFR and HER2 and downregulation of HER3 in prostate cancer lymph node metastases compared with corresponding primary tumors

Abstract: Abstract. The epidermal growth factor receptor (EGFR) family members are potential targets for therapy using extracellular domain receptor binding agents, such as the antibodies trastuzumab and cetuximab, or antibodies labeled with therapeutically useful radionuclides or toxins. This is especially the case when the tumor cells are resistant to chemotherapy and tyrosine kinase inhibitors. Studies concerning the expression of these receptors in prostate cancer vary in the literature, possibly due to differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…These results are similar to those obtained by CARLSSON et al (2013) in their study with human PC and lymph node metastasis. They observed EGFR immunostaining in roughly 41% of primary tumors, and in one case of metastasis.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These results are similar to those obtained by CARLSSON et al (2013) in their study with human PC and lymph node metastasis. They observed EGFR immunostaining in roughly 41% of primary tumors, and in one case of metastasis.…”
Section: Discussionsupporting
confidence: 82%
“…The samples were scored 1+, and considered negative. Faleiro et al CARLSSON et al (2013) reported that Her2 immunostaining may occur in normal tissues. Likewise, the IHC results concerning Her2 were in keeping with those obtained with RT-PCR technique, since there was no expression of ErbB2 in normal prostatic tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations